23.0k views
5 votes
I need help with several math problems it says given f(x)=2-3x and g (x) = -x-1 Find the following and Simplify when possible. 1. (f-g) (-3) 2. (f-g) (x) 3. (f × g) (-1) d. (f ×g) (x) E. f (x-1) F. f (x-1)-f (1) G. g(x+2)-g (2) h. g (x+h) - g(x) ​

1 Answer

6 votes

Answer:

Explanation:

Given:


f(x) = 2 - 3x


g(x) = -x - 1

1.
(f-g) =
2 - 3x - ( -x - 1 )


(f-g) = 2 - 3x + x + 1


(f-g) = 3 - 2x

therefore :
(f-g) (-3) means that we are substituting - 3 for x , that is


(f-g)(-3) =
3 - 2 ( - 3 )


(f-g)(-3) =
3+6


(f-g)(-3) =
9

2.
(f-g)(x) = 3 - 2x

3. (
f x
g ) =
(2-3x)(-x-1)

(
f x
g ) =
2(-x-1) -3x(-x-1)

(
f x
g ) =
-2x - 2
+ 3x^(2)+3x

(
f x
g ) =
3x^(2)+x - 2

Therefore :

(
f x
g )
(-1) =
3(-1)^(2)
+(-1) - 2

(
f x
g )
(-1) =
3 - 1 - 2

(
f x
g )
(-1) =0

4. (
f x
g )(x) =
3x^(2)+x - 2

5.
f(x-1) , this means that we will substitute
x-1 for
x in
f(x) , that is


f(x-1) =
2 - 3(x-1)


f(x-1) =
2 - 3x + 3


f(x-1) =
5 - 3x

6.
f(x-1)
-f(1) =
5 - 3x
- (2-3(1) )


f(x-1) - f(1) =
5 - 3x +1


f(x-1) - f(1) =
6 - 3x

7.
g(x+2)- g(2)


g(x+2) = -(x+2) - 1


g(x+2) =
-x-2-1


g(x+2) =
-x - 3


g(2) = -2-1 = -3

Therefore :


g(x+2)- g(2) =
-x - 3 -(- 3)


g(x+2)- g(2) =
-x

8.
g(x+h) - g (x)


g(x+h) = -(x+h) - 1 = -x - h - 1

Therefore :


g(x+h) - g (x) =
-x - h - 1 -
(-x-1)


g(x+h) - g (x) =
-x - h - 1 + x + 1


g(x+h) - g (x) =
-h

User Sam Baumgarten
by
5.9k points